A new method for the evaluation of the ultimate seismic capacity of rectangular underground structures. Issue 126 (November 2019) - Lu, Dechun; Ma, Chao; Du, Xiuli; Wang, Xin
Abstract: The ultimate seismic capacity of underground structures should be known to provide a sufficient seismic resistance during the seismic design, due to the irreparable and difficulty of reconstruction after collapsed. However, existing single-factor evaluation methods, including inter-story drift ratio, stress, strain, etc., only present the serviceability seismic capacity and cannot reflect the seismic damage mechanism of underground structures. This paper proposes a performance-based evaluation method to assess the ultimate seismic capacity of rectangular underground structures by considering both the characteristics of the structure itself and earthquake loadings. Ultimate horizontal deformation capacity envelope and failure ratio, derived from the seismic collapse mechanism of rectangular underground structures, are the key assessment parameters of the ultimate seismic capacity. Because the horizontal deformation capacity of the underground structures affected by the vertical loads was taken into account, the obtained ultimate seismic capacity is a band range and expressed with the PGA of earthquakes. The detailed procedure of the evaluation method is demonstrated step by step. Afterwards, a case study is presented to evaluate the ultimate seismic capacity of Daikai station influenced by the spectral characteristics and duration of earthquakes. The predominant periods of earthquakes which the structure might be sensitive to are discussed. The proposed method provides a detailed understanding of the performance-based seismic evaluation of rectangular underground structures and can be extended to characterize other seismic performance levels of the rectangular underground structures in the future work. Highlights: Ultimate seismic capacity of rectangular underground structures. Critical component for the seismic design. Horizontal deformation capacity and failure ratio of underground structures. Band range of the ultimate seismic capacity expressed with PGA.